Neuromorphic network implementation of the somatosensory cortex - Joshi, Jonathan; Parker, Alice C.; Celikel, Tansu (2013 6th International IEEE/EMBS Conference on Neural Engineering (NER), 2013)
A first-order neuromorphic implementation of structural plasticity is shown. Our circuit models spiking behavior of somatosensory neurons and neuronal receptive fields in the upper layers of the rodent barrel (somatosensory) cortex while replicating biological observations of experience-dependent changes in receptive field organization, network topology and synaptic connectivity in silico. Anatomical changes in synaptic connectivity have been modeled using analog switching, based on changes in neural activity. We demonstrate the effects of loss of inhibition and sensory (whisker) inputs with our circuits.